Minimum Design : Philippe Starck - Morozzi, Cristina (24 ORE Cultura, 2011)
Philippe Starck is one of the world's most prolific and famous designers. Well known for his luxurious hotels and restaurants, he is equally celebrated for his inspirational reworkings of everyday household items. Whether it be his iconic lemon squeezer, dubbed the 'Juicy Salif', or his colourful stylized toothbrushes, Starck's works are some of the earliest examples of 'democratic design'. This idea, that exceptional products should not be exclusive and elite, but be accessible and affordable, would eventually revolutionise modern design. Starck has worked privately for French president Francois Mitterand, decorating a suite in the Palais d'Élysée in Paris in 1982. He has designed products for a number of internationally renowned organisations including Microsoft, Lacie, Eurostar, Alessi and Fossil.
Serie Minimum Design o.l.v. Andrea Branzi
Engels
gebonden, hardback
boek
Keywords: Starck, Philippe; Eigen Tijd; Frankrijk